2006
DOI: 10.1161/circulationaha.106.638460
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Sulfoxide Inhibits Tissue Factor Expression, Thrombus Formation, and Vascular Smooth Muscle Cell Activation

Abstract: Background-Subacute stent thrombosis is a major clinical concern, and the search for new molecules to cover stents remains important. Dimethyl sulfoxide (DMSO) is used for preservation of hematopoietic progenitor cells and is infused into patients undergoing bone marrow transplantation. Despite its intravenous application, the impact of DMSO on vascular cells has not been assessed. Methods and Results-In human endothelial cells, monocytes, and vascular smooth muscle cells (VSMC), DMSO inhibited tissue factor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 40 publications
6
69
0
3
Order By: Relevance
“…DMSO was previously suggested to inhibit platelet activation; however, this was postulated only indirectly and without any molecular insights [6,8]. In this study, we for the first time can clearly demonstrate that DMSO inhibits platelet adherence and platelet aggregation which are essential steps for the physiological and pathophysiological formation of a stable occlusive thrombus [24].…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…DMSO was previously suggested to inhibit platelet activation; however, this was postulated only indirectly and without any molecular insights [6,8]. In this study, we for the first time can clearly demonstrate that DMSO inhibits platelet adherence and platelet aggregation which are essential steps for the physiological and pathophysiological formation of a stable occlusive thrombus [24].…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, in previous in vitro studies we have shown that DMSO concentrations up to 1% are not toxic for human endothelial cells, smooth muscle cells and peripheral blood monocytes [6].…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations